MODELING OF PROCESSES OF DETAILS HEATING AND COOLING OF DETAILS ON THE BASIS OF THE THREE-DIMENSIONAL EQUATION OF HEAT CONDUCTIVITY IN CAE «PROTERM-І» - A. N. Chichko; D. M. Kukuj; V. F. Sobolev; S. G. Lihouzov; O. A. Sachek (Литьë и металлургия)
The mathematical apparatus for calculation of process of thermal heating and cooling of the detail which is situated in modeling environment of the furnace is presented. Modules of the software “ProTerm-1” in the environment of visual programming Delphi 7.0 for operating system Windows 95/98/2000XP vista are described.